Ideologi dalam Desain Komunikasi Visual - REZA APRIANTI (Komunikator, 2013)
Ideology will have power if it can be represented and communicated. Ideology is full of interest including ideology which is owned by media. This ideology makes the media not neutral. This study was conducted based on the view of James Lull. The object of the study was the pictures of 2009 presidential candidates who became the front cover of Koran Tempo. It was expected to be able to explain how ideology works in the visual communication design (pictures) without using verbal language. By using semiotic analysis, this study was able to reveal it. To facilitate the research, the object of this study was divided into six units of analysis which consists of theme object, verbal text, visualization, composition, readers’ point of view (viewers) and modalities. Based on the research result, it could be concluded that the transformation process in ideology of interest from both internal and external sides of Koran Tempo in reporting the 2009 presidential candidates also occurred in the form of visual communication. It was designed to look as neutral as possible so that it could get into the readers’ subconscious without coercion. Keywords: Ideology of media, visual communication design